ANALISIS PERILAKU KONSUMEN KOTA BOGOR TERHADAP PRODUK KOSMETIK HIJAU - Nadya Tanaya Ardianti; Idqan Fahmi; Anny Ratnawati (Jurnal Manajemen & Agribisnis, 2008)
The exploding societal movement based upon environmental concerns and consumer awareness is spreading all over the globe. As a result, consumers concern about environmental issues is growing significantly and marketers have realized the importance of introducing green cosmetic products.However, there is doubt whether this awareness and concern is translated into the right behavior. In this study, consumers’ attitudes, behaviors, perception and demographic factor were manipulated to determine their relative influence on willingness to pay for green cosmetic products. The results showed consumer’s age, education, income and ecoliteracy to be the consistent explanatory factor in predicting their willingness to pay. The result also suggested that attitude toward firm’s responsibilities and buying behavior which’s consider environment factor to be the consistent explanatory factor in predicting their willingness to pay. This study also examined the relationships between consumer’s attitude, subjective norms, perceived behavior control and green cosmetic buying intentions using the Theory of PlannedBehavior (TPB). This study revealed that at significance level ten percent, attitude, subjective norm and perceived behavior control correlates positively with intention.